Marketing of household toilets in Ghana - Amaka E.U. Obika; Joseph Boateng; Alhassan J. Kanu; Oliver Frimpong (2003)
This paper describes a research on the application of commercial marketing approach to sanitation. The research project is being conducted in Nkawie/Toase, a small town in Ghana by WEDC; LSHTM, and TREND (a local NGO based in Kumasi, Ghana) in collaboration with the Atwima District Assembly. The research is still on going; therefore this paper presents the process that is being implemented and some of the results.